Implementasi Budaya Literasi dalam Meningkatkan Karakter Religius Siswa - Hayati, Mardhiah (Al-Miskawaih: Journal of Science Education, 2023)
This article discusses students' interest in reading through religious activities at State Vocational School 2, Jambi City. The main problem that will be discussed is why is the implementation of literacy culture in improving students' religious character still low? This article comes from qualitative research using data collection techniques through observation, interviews and documentation. The research results show that religious character is formed from several religious literacy activities at this school such as reading and understanding the Al-Qur'an. Supporting factors for the Implementation of Literacy Culture in Improving the Religious Character of Students in this school include; first, teacher participation in carrying out religious activities, second, the solidarity of all teachers to form religious character in children, and third, the existence of adequate school facilities and infrastructure. While the inhibiting factors include; firstly, some students are disorganized and deliberately do not participate in religious activities, secondly, environmental factors are less supportive, and thirdly, students' weak ability to read the Koran. Artikel ini membahas minat baca siswa melalui kegiatan religius di Sekolah Menengah Kejuruan Negeri 2 Kota Jambi. Permasalahan utama yang akan dibahas adalah mengapa implementasi budaya literasi dalam meningkatkan karakter religius siswa masih rendah? Artikel ini berasal dari penelitian kualitatif dengan teknik pengumpulan data secara observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa karakter religius dibentuk dari beberapa kegiatan Litereasi religius di sekolah ini  seperti membaca dan memahami Al-Qur`an. Faktor pendukung dari Implementasi Budaya Literasi dalam Meningkatkan Karakter Religius Siswa di sekolah ini antara lain; pertama, partisipasi guru dalam melaksanakan kegiatan religius, kedua, kekompakan seluruh guru untuk membentuk karakter religius pada anak, dan ketiga, adanya sarana dan prasarana sekolah yang memadai. Sedangkan faktor penghambatnya antara lain; pertama, sebagian siswa tidak tertib dan sengaja tidak mengikuti kegiatan keagamaan, kedua, faktor lingkungan yang kurang mendukung, dan ketiga, lemahnya kemampuan siswa dalam membaca Al-Qur'an.